Evaluation of the California Mental Health Services Authority's Prevention and Early Intervention Initiatives - Burnam, M. Audrey; Berry, Sandra H.; Cerully, Jennifer L.; Eberhart, Nicole K. (RAND Corporation, 2023)
Provides a summary and commentary on a more detailed RAND interim evaluation of the California Mental Health Services Authority statewide prevention and early intervention program.